2021
DOI: 10.2196/26744
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Noninvasive Telemonitoring for Chronic Heart Failure on Health Care Utilization: Systematic Review

Abstract: Background Chronic heart failure accounts for approximately 1%-2% of health care expenditures in most developed countries. These costs are primarily driven by hospitalizations and comorbidities. Telemonitoring has been proposed to reduce the number of hospitalizations and decrease the cost of treatment for patients with heart failure. However, the effects of telemonitoring on health care utilization remain unclear. Objective This systematic review aims … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 58 publications
(214 reference statements)
1
24
0
Order By: Relevance
“…Remote monitoring as a feature of eHealth interventions may include parameters for detecting symptom and illness deterioration, successfully reducing readmissions among patients with HF [ 19 - 21 ]. However, in our study, the effects on readmissions from remote monitoring were inconclusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remote monitoring as a feature of eHealth interventions may include parameters for detecting symptom and illness deterioration, successfully reducing readmissions among patients with HF [ 19 - 21 ]. However, in our study, the effects on readmissions from remote monitoring were inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent reviews have summarized the findings from eHealth follow-up interventions for patients with HF and provided information about the efficiency of such interventions. Auener et al [ 19 ] investigated the effects of telemonitoring programs on different aspects of health care use from 16 randomized controlled trials (RCTs) and 13 nonrandomized studies. All studies included weight as a parameter, whereas only 4 included electrocardiography measures as a physiological parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Quadruple Aim). Although most evidence syntheses report mostly positive outcomes (Bashi et al, 2017;Clark et al, 2007;Farias et al, 2020;Nick et al, 2021;Pandor et al, 2013;Taylor et al, 2021;Vegesna et al, 2017), others have also reported mostly null, inconclusive, or underwhelming results (Auener et al, 2021;Baltaxe et al, 2019;Flodgren et al, 2015;Noah et al, 2018). A common limitation is that RPM programmes can vary greatly, including the modality, timing, and types of data collection/transfer, the degree to which RPM is incorporated into routine care, and the investment in implementation supports such as patient and provider training (Flodgren et al, 2015;Nick et al, 2021;Vegesna et al, 2017).…”
Section: Remote Patient Monitoringmentioning
confidence: 99%
“…, 2021; Vegesna et al. , 2017), others have also reported mostly null, inconclusive, or underwhelming results (Auener et al. , 2021; Baltaxe et al.…”
Section: Introductionmentioning
confidence: 99%
“…A capitated telehealth coaching service did not reduce hospital readmissions; however, there was a reduction in acute hospital bed days [ 3 ]. In patients with heart failure, a systematic review found that a reduction in hospitalizations was accompanied by an increase in nonemergency outpatient visits [ 4 ]. Glycemic therapy frequently requires revision during hospital stay [ 5 ].…”
Section: Introductionmentioning
confidence: 99%